Investigation of thermal entropy generation and nanofluid flow in a new heatsink with effect of nanoparticles shape. (August 2022) - Alqaed, Saeed; Mustafa, Jawed; Aybar, Hikmet Ş.; Jamil, Basharat; Alharthi, Mathkar A.
Abstract: In this paper, the entropy generation (ENT) in two novel micro heatsinks (MHSs) is investigated numerically. The HSs are two types of octagonal ones with circular and rectangular fins. Water/alumina boehmite nanofluid (NF) is used as a cooling fluid for HSs, which enters from the middle of the heatsink (HS) and exits from four side outputs. The Reynolds number (Re) varies from 300 to 1700 and the concentration of nanoparticles (NPs) changes from 0 to 6%. The shapes of NPs include platelet brick, blade, cylinder, and Oblate Spheroid (OS). A heat flux due to the operation of a microprocessor is applied to the bottom of the HSs made of copper. The finite element method is used for the simulations. The variables include pumping power (PP), ENT, ENT due to fluid friction, thermal ENT, temperature gradient contours, etc. The results of this study show that less ENT occurs in the HS with rectangular fins and less PP occurs in the HS with circular ones. Increasing the Re reduces the amount of ENT and increases the PP. The results demonstrate that the addition of NPs with high volume percentages is not suitable in terms of ENT and PP.